2018
DOI: 10.1002/pd.5326
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia has a better prognosis when associated with a hernia sac

Abstract: The presence of a hernia sac in CDH is associated with better outcome, especially survival at 6 months. If the presence of a hernia sac is recognized as a particular entity, which carries a good prognosis, it is necessary to be able to diagnose it prenatally, especially in the era of prenatal fetal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…A particular strength of our work and its findings reported here is the comparatively longer duration of patient follow-up compared with other published studies. [12][13][14][15][16][17][18] The effect size or survival difference(s) in CDH neonates identified to have a sac at operation compared with no sac at our United Kingdom center is not significant in contrast to previous studies examining this issue with shorter patient follow-up. This is, despite our series, being the largest reported and thus having the greatest statistical power to detect a potential difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A particular strength of our work and its findings reported here is the comparatively longer duration of patient follow-up compared with other published studies. [12][13][14][15][16][17][18] The effect size or survival difference(s) in CDH neonates identified to have a sac at operation compared with no sac at our United Kingdom center is not significant in contrast to previous studies examining this issue with shorter patient follow-up. This is, despite our series, being the largest reported and thus having the greatest statistical power to detect a potential difference.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other publications have reported the association of hernia sac in CDH with either improved survival or other surrogate measures associated with better outcomes. [13][14][15][16][17][18] It has been proposed that the distinction between CDH with sac and diaphragm eventration is not clear and there does appear to be some confusion in the literature likely originating from an incomplete understanding of the embryology and the urge to classify and discretize a continuum. The etiology of a Bochdalek diaphragmatic hernia is widely believed to be due, in part, to the embryological failure of fusion of the pleuroperitoneal membranes or when a sac is present, consisting solely of a pleuroperitoneal membrane with complete failure of muscularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that low birthweight, prematurity, large defect size, right sided defects, liver herniation, absence of a hernia sac, and severe pulmonary hypertension have a negative impact on neonatal outcomes. 2,3,13,[20][21][22][23][24][25][26][27][28][29] For example, the presence of a hernia sac in CDH has been associated with decreased time spent on ventilation, 30 and the presence of severe pulmonary hypertension has been associated with mortality. 22,31 Despite the previously reported associations with poor neonatal outcomes, we found that only lower birthweights and lower gestational ages were associated with worse respiratory outcomes between 0 and 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a hernia sac predicts better survival [71,72]. The location of fetal stomach, such as intraabdominal, anterior left chest, posterior-mid left chest or retro cardiac, has been shown to strongly predict neonatal outcomes in isolated left CDH [73][74][75].…”
Section: Assessment Of Lung Size Indirect Methodsmentioning
confidence: 99%